Intracellular VEGF regulates the balance between osteoblast and adipocyte differentiation - Liu, Yanqiu (American Society for Clinical Investigation, 2012)
Osteoporotic bones have reduced spongy bone mass, altered bone architecture, and increased marrow fat. Bone marrow stem cells from osteoporotic patients are more likely to differentiate into adipocytes than control cells, suggesting that adipocyte differentiation may play a role in osteoporosis. VEGF is highly expressed in osteoblastic precursor cells and is known to stimulate bone formation. Here we tested the hypothesis that VEGF is also an important regulator of cell fate, determining whether differentiation gives rise to osteoblasts or adipocytes. Mice with conditional VEGF deficiency in osteoblastic precursor cells exhibited an osteoporosis-like phenotype characterized by reduced bone mass and increased bone marrow fat. In addition, reduced VEGF expression in mesenchymal stem cells resulted in reduced osteoblast and increased adipocyte differentiation. Osteoblast differentiation was reduced when VEGF receptor 1 or 2 was knocked down but was unaffected by treatment with recombinant VEGF or neutralizing antibodies against VEGF. Our results suggested that VEGF controls differentiation in mesenchymal stem cells by regulating the transcription factors RUNX2 and PPARγ2 as well as through a reciprocal interaction with nuclear envelope proteins lamin A/C. Importantly, our data support a model whereby VEGF regulates differentiation through an intracrine mechanism that is distinct from the role of secreted VEGF and its receptors.